2017
DOI: 10.1007/s11255-017-1555-5
|View full text |Cite
|
Sign up to set email alerts
|

Association of podocyte autophagosome numbers with idiopathic membranous nephropathy and secondary membranous nephropathy

Abstract: The results indicated that the autophagy participated in the podocyte injury in IMN and sMN and the number of autophagosomes in podocytes was related to the pathological classification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…The conversion of LC3-I to LC3-II indicates autophagosome formation [ 16 ] and enhanced autophagy [ 17 ]. Additionally, TEM is the frequently used to monitor autophagosomes in addition to LC3 [ 18 , 19 ]. We observed increased LC3-II and LC3-II/LC3-I ratio in the cisplatin group compared to the control group suggesting that autophagy was activated in response to cisplatin.…”
Section: Discussionmentioning
confidence: 99%
“…The conversion of LC3-I to LC3-II indicates autophagosome formation [ 16 ] and enhanced autophagy [ 17 ]. Additionally, TEM is the frequently used to monitor autophagosomes in addition to LC3 [ 18 , 19 ]. We observed increased LC3-II and LC3-II/LC3-I ratio in the cisplatin group compared to the control group suggesting that autophagy was activated in response to cisplatin.…”
Section: Discussionmentioning
confidence: 99%
“…They are highly specialized cells involved in the charge and size filtration characteristics of the glomerulus. When stimulated with pathogens, podocytes might protect themselves through autophagy [24]. In this study, cultured human podocytes were treated primarily by autoantibodies from serum from patients with LN, inducing autophagy flux and producing foot process injury.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Cina et al reported that autophagy may play a fundamental role in mouse podocyte differentiation and recovery from puromycin aminonucleoside (PAN)-induced injury [10]. In addition, we previously found that autophagy participated in idiopathic membranous nephropathy (IMN)-induced podocyte injury, and the number of autophagosomes in podocytes was related to the level of pathology [11].…”
Section: Introductionmentioning
confidence: 98%